Subsurface Profile Analysis for Aquifer Layer Identification: Analisis Profil Bawah Permukaan untuk Identifikasi Lapisan Pembawa Air - Syarifullah Bundang; Muhammad Fawzy Ismullah Massinai; Firman Firman; Wahyu Hidayat (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
Bungaiya village is a village located in Gowa Regency which has volcanic rock lithology with one of the problems faced in volcanic rocks is that the rock porosity is small so that this layer cannot be an aquifer zone. But the water needs needed by the community for agriculture are very large. Geoelectric is a geophysical method that can be used to describe subsurface profiles, especially aquifer layers. The purpose of this study is to interpret using the geoelectric resistivity method, is the Wenner configuration method as many as 2 lines with a length of 470 m and a space of 10 m. The interpretation results on Line 1, there are 3 layers, are volcanic breccia with resistivity values ​​of 85.6 – 2.2013.19 Ωm and depths between 1.2 – 68 m, layer 2 of tuff with resistivity values ​​of 9.82 – 59.68 Ωm, depth of 12 – 76 m and the third layer is a volcanic breccia, resistivity value is 85.6 – 176 Ωm. Line 2 has 2 layers, are the first layer with a depth of 1.2 – 42 m with a resistivity value of 93 – 490.41 Ωm which is a volcanic breccia. The second layer at a depth of 1.2 – 78.8 m with a resistivity value of 30.9 – 77, 67 Ωm is tuff. Layers 1 and 2 show a similar subsurface profile. Based on these results, it can be concluded that the layer that functions as a water-carrying layer is tuff with a resistivity value of 9.82 – 77.67 Ωm.